Business Processing Reengineering failure at TELECO: A PMBOK-An Inspired Analysis of How Project Managers Overcome IT Challenges - Muhammad Izzuddin Mohsin; Muhammad Nazrul Alif Baharudin; Saiful Arieff Ahmad Ridauddin; Amir Imtiaz Mohamad; Nur Sazlin Syafika Mazlan; Muhammad Hassif Mas Fawzi; Muhammad Faiz Hamdan; Nur Alisya Nadira Mohd Sukeri; Nurliyana Sulaiman (Applied Information Technology And Computer Science, 2023)
This study delves into the challenges faced by TELECO’s Business Process Reengineering (BPR) initiative, particularly employee resistance, IT over-reliance, and issues in project management. This research aims to analyze these hurdles within the framework of the Project Management Body of Knowledge (PMBOK). Risk management, scope management, integration, communication, and human resources aspects are explored by employing a comprehensive methodology. Key findings highlight the critical role of effective project management in navigating complexities. The study suggests a focus on change management, clear communication, and employee welfare to ensure successful organizational transformations. This examination of TELECO’s experience serves as a valuable case study, emphasizing the strategic importance of project management in dynamic industries.